Optic nerve sheath diameter measured using early unenhanced brain computed tomography shows no correlation with neurological outcomes in patients undergoing targeted temperature management after cardiac arrest. (July 2018) - Lee, Dong Hoon; Lee, Sun Hwa; Oh, Je Hyeok; Cho, In Soo; Lee, Young Hwan; Han, Chul; Choi, Wook Jin; Sohn, You Dong; ,
Abstract: Aim: Previous studies indicated that the optic nerve sheath diameter (ONSD) measured using brain computed tomography (CT) is a prognostic factor for poor neurological outcome after cardiac arrest. However, these studies were retrospective or included a small sample size. We performed a prospective multi-centre observational study to investigate the correlation between the ONSD on early brain CT and neurological outcomes in patients undergoing targeted temperature management (TTM). Methods: This study used data from the Korean Hypothermia Network prospective registry between November 2015 and October 2016. Out-of-cardiac arrest patients who underwent brain CT within 2 h after return of spontaneous circulation (ROSC) were included. The primary endpoint was neurological outcomes at 6 months (cerebral performance category; CPC); the secondary outcome was hospital mortality. The ONSD was measured using unenhanced brain CT images. Results: In total, 374 patients were included from 18 hospitals, and 329 underwent CT within 2 h after ROSC. Six months after cardiac arrest, good (CPC 1–2) and poor (CPC 3–5) neurological outcomes were observed in 99 (30.09%) and 230 (69.91%) patients, respectively. There was no significant difference in the ONSD between groups (good outcome group: 5.61 ± 0.59 mm, poor outcome group: 5.69 ± 0.79 mm; p = 0.275), nor between discharged patients who survived and those with hospital mortality (5.63 ± 0.64 mm and 5.70 ± 0.67 mm, respectively, p = 0.399). Conclusion: The ONSD on initial brain CT after ROSC was not correlated with neurological outcome at 6 months in patients who underwent TTM.